Effect of Nickel-Chromium and Non-Precious Gold Color Alloy Cast Posts on Fracture Resistance of Endodontically Treated Teeth - Gholami, Fatemeh; Kohani, Parisa; Aalaei, Shima (Iranian Endodontic Journal, 2017)
Introduction: Root canal-treated teeth are weaker than vital teeth and are more susceptible to fractures. Therefore, special precautions should be adhered to, such as the use of various types of cast or prefabricated posts. Regarding the effect of post material on fracture resistance of teeth, the aim of this in vitro study was to evaluate the effect of non-precious gold color alloy (NPG) and nickel-chrome (Ni-Cr) cast posts on resistance of endodontically treated teeth. Methods and Materials: In this study, 30 freshly extracted single-rooted premolar teeth were randomly divided into two groups. After root canal treatment, post patterns were made with Duralay in group 1 and cast with Ni-Cr alloy; in group 2, the patterns were cast with NPG alloy. Zinc phosphate cement was used for cementation in this study. Shear force was applied at 1 mm/min at 45ºC to the buccal cusps until root fracture occurred. Independent sample t test was used for data analysis by using SPSS version 21. The level of significance was set at 0.05. Results: Mean fracture resistance values were 1380±454 N for Ni-Cr versus 1964±640 N for NPG, with significant differences (P=0.007). Conclusion: The fracture resistance of endodontically treated teeth with non-precious gold color alloy cast post was higher than that of endodontically treated teeth with Ni-Cr cast post. Keywords: Alloys; Casts; Fracture; Nickel-Chromium; Resistance